اختبار فرضية كفاءة الصيغة الضعيفة للسوق المالي الإسلامي-مؤشر السوق داوجونز الاسلامي- - عيساوي, سهام (جامعة الوادي - University of Eloued, 2022)
تبحث هذه الورقة البحثية في اختبار كفاءة السوق المالي الإسلامي من خلال إحدى مستوياتها وهي الصيغة الضعيفة، من خلال المشاهدات اليومية لمؤشر السوق داوجونز الإسلامي من 01 سبتمبر 2019 إلى غاية 14 ديسمبر 2019، وذلك باستخدام اختبارات إحصائية لدراسة استقرارية واستقلالية السلسلة وكذا دراسة التوزيع الطبيعي لها، وتشير النتائج أن سلسلة الدراسة مستقلة عن بعضها البعض ومستقرة وبالتالي فالسوق المالي الإسلامي يتميز بكفاءة في ظل المستوى الضعيف This research paper examines the testing of the efficiency of the Islamic financial market through one of its levels, which is the weak formula, through the daily views of Dow Jones Islamic Market Index from 01 September 2019 to 14 December 2019, by using statistical tests to study the stability and independence of the chain as well as the study of its natural distribution. The results indicate that the study series is independent from one another and stable and therefore the Islamic financial market is characterized by efficiency in light of the weak level
Testing weak Form of efficiency hypothesis in the Islamic financial market - Dow Jones Islamic Market Index
مقال
Keywords: داوجونز إسلامي؛ مؤشر؛ كفاءة؛ أسواق الاسلامية.